Consumer motivation and service quality in using luxurious wedding decoration - Ibnu Aziz Manazam; Monika Tiarawati (Yayasan Ilomata, 2021)
This study aims to determine: (1) the influence of consumer motivation on purchasing decision for luxurious wedding decorations, (2) the effect of service quality on purchasing decision for luxurious wedding decorations. This study is a conclusive research. Non-probability sampling was used as a sampling technique with the census method on 122 respondents. Respondents are consumers who have already purchased and made their own decision in purchasing at Garda Dekorasi from 2018 through April 2019. The questionnaire distribution was performed online using a google form. The measurement scale used in this study was Likert scale. Statistical analysis used is multiple linear regression analysis, performed using SPSS 23. The results showed that the consumer motivation variable has a positive and significant influence on purchasing decision, and service quality has a positive and significant influence on purchasing decision. The results also show that service quality has a greater influence on purchasing decision compared to consumer motivation.